1986
DOI: 10.4319/lo.1986.31.3.0457
|View full text |Cite
|
Sign up to set email alerts
|

Fish‐flamingo‐plankton interactions in the Peruvian Andes1

Abstract: The zooplankton and flamingo populations of 20 high elevation (3,700-4,700 m) lakes in the Andes of southern Peru were assessed on one to three occasions each. Some of these lakes have cyprinodont fish (Orestias spp.), others do not. Lakes with fish usually have a sparse zooplankton dominated by cyclopoid copepods and chydorid cladocerans; the others tend to have an abundant zooplankton dominated by Calanoid copepods and daphnids or by Artemia. Chilean flamingos (Phoenicopterus chilensis) are usually absent or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 18 publications
1
58
0
3
Order By: Relevance
“…One important result is the presence together of the halophylic copepod B. poopoensis and Artemia in De Los Cisnes lagoon at the time of collection, something unexpected (Hurlbert et al, 1986), though a similar finding of non coexistence was reported for shallow saline lakes in central Argentina (Echaniz et al, 2006;Vignatti et al 2007) and Altiplano (De los Rios and Gajardo, 2010). As supposed by Hurlbert et al (1986) Artemia and halophylic copepods (in example B. poopoensis) would not coexist because copepods would predate Artemia nauplius.…”
Section: Heterogeneidade Potencial Em Associações Crustáceas Do Zooplmentioning
confidence: 79%
See 1 more Smart Citation
“…One important result is the presence together of the halophylic copepod B. poopoensis and Artemia in De Los Cisnes lagoon at the time of collection, something unexpected (Hurlbert et al, 1986), though a similar finding of non coexistence was reported for shallow saline lakes in central Argentina (Echaniz et al, 2006;Vignatti et al 2007) and Altiplano (De los Rios and Gajardo, 2010). As supposed by Hurlbert et al (1986) Artemia and halophylic copepods (in example B. poopoensis) would not coexist because copepods would predate Artemia nauplius.…”
Section: Heterogeneidade Potencial Em Associações Crustáceas Do Zooplmentioning
confidence: 79%
“…As supposed by Hurlbert et al (1986) Artemia and halophylic copepods (in example B. poopoensis) would not coexist because copepods would predate Artemia nauplius. Regarding this point, we do not know if this predation ability is associated to A. franciscana exclusively, whilst this could not be the case for A. persimilis.…”
Section: Heterogeneidade Potencial Em Associações Crustáceas Do Zooplmentioning
confidence: 99%
“…Although the lake then became hyposaline (Hammer 1986), the redissolution of salts from sediments caused a three-fold increase in the saline concentration, without large fluctuations in the depth, and thus, the salinity reached the mesosaline level in the last month of the study (Vignatti et al 2012). Salinity is an abiotic factor that can determine the zooplankton assemblage of South American aquatic ecosystems (Hurlbert et al 1986, Williams et al 1995, De los Ríos & Crespo 2004, Vignatti 2011, Battauz et al 2013, and therefore, one reason why B. poopoensis was recorded as present from October onwards, might be due to the recorded presence of Boeckella gracilis until the previous month, which is a much less salinity-tolerant species but a potential competitor of B. poopoensis. In these environments, which generate high physiological stress to organisms, species such as B. poopoensis might possess an adaptive advantage, since their ability to tolerate increased salinity allows them to find refuge against competition or predation by some fish (Herbst 2001, Santangelo et al 2008, but not by flamingos (Battauz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In South America, shallow temporary lakes are abundant and are located mainly in tropical and subtropical latitudes of the Andes (Hurlbert et al 1986, Williams et al 1995, De los Ríos & Crespo 2004, in the center and northwest of the Pampa Plains (Quiró s 1997) and in the Patagonian plateau (Soto et al 1994, Campos et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the present results, two main forces likely regulate aquatic community structure: salinity variation and predator presence. Such a combination of factors have been reported in shallow Andean mountain saline and sub-saline lakes (Hurlbert et al, 1986; De los Ríos-Escalante, 2011).…”
Section: Salinity Altitudementioning
confidence: 99%